Tracing education policy: Selections from the oxford review of education - Phillips, D; Walford, G (Taylor and Francis, 2013)
This book brings together key articles that trace the development of British education policy since 1975 and provides a valuable route map to developments within education policy during this period. It includes twenty-six seminal articles from the Oxford Review of Education written by many of the leading authors in the field and covering issues and topics with a wide significance beyond Britain.